DYNAMICS OF ROLES IN THE TRADITION OF HUMMING IN THE MIDST OF SOCIAL CHANGE IN PAKPAK SOCIETY - Muhammad Rifai; Lister Berutu; Tri Presar Jhon Tuan Panjaitan; Maulida Masyitoh; Tresno Tresno (Jurnal Ilmiah Sosiologi Agama (JISA), 2026)
The traditional ceremony of mengerumbang is one of the important traditional rites in Pakpak society, carried out by elderly individuals as a form of repayment of traditional debts to hula-hula before death. This study aims to examine the symbolic meaning, social structure, and socio-cultural function of the mengerumbang ceremony in the context of contemporary Pakpak society and to observe the role of this tradition. The research method uses a qualitative approach with ethnographic methods through participatory observation, in-depth interviews with traditional leaders and ritual practitioners, and documentary studies of local customs and practices. The results of the study show that mengerumbang is not merely a customary ritual, but a social mechanism to maintain the honour of individuals and families, strengthen the continuity of the sulang silima kinship system, support economic redistribution through customary gifts, and legitimise a person's social status within the Pakpak customary structure. Furthermore, changes in ritual practices due to the influence of religion and modernisation indicate a dynamic process of cultural adaptation without eliminating the core meaning of the custom. Thus, mengerumbang functions as a space for negotiation between tradition, identity, and social change in Pakpak society.